2006
DOI: 10.1111/j.1540-8159.2006.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Atrial Thrombus Formation and Atrial Appendage Function in Patients with Pacemaker by Transesophageal Echocardiography

Abstract: Long-term loss of AV synchrony induced by VVI pacing is associated with the impairment of LAA contraction. Thrombus formation in the LAA is not increased by VVI pacing in patients with relatively good left ventricular (LV) function and sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[27] Another study demonstrated a decrease in the left atrial appendage flow velocity during ventricular pacing. [28] NSVT causes ventricular dyssynchrony and may contribute to mechanical abnormalities in the left atrial appendage, which might explain the potential for enhanced stroke/thromboembolic event. To the best of our knowledge, this study is the first investigation demonstrating that NSVT in the structural normal heart was a marker related to other stroke-causing diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Another study demonstrated a decrease in the left atrial appendage flow velocity during ventricular pacing. [28] NSVT causes ventricular dyssynchrony and may contribute to mechanical abnormalities in the left atrial appendage, which might explain the potential for enhanced stroke/thromboembolic event. To the best of our knowledge, this study is the first investigation demonstrating that NSVT in the structural normal heart was a marker related to other stroke-causing diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Aslanabadi et al 1 observed that percutaneous transvenous mitral commissurotomy boosts the LAA function as it improved the LAA ejection fraction and emptying velocity after intervention in patients with rheumatic heart disease independent of rhythm status (NSR versus AF). In contrast, Alizadeh et al 21 showed that the implementation of pacing using VVI mode impaired the LAA function, but it did not increased the thrombus formation within the LAA. These findings designate that LAA remodeling in individuals with AF happened during the transition from sinus rhythm to fibrillation.…”
Section: Discussionmentioning
confidence: 91%
“…One of the frequent structural changes seen in patients with ventricular cardiomyopathy is ventricular dilatation, which is known to provoke the stasis of blood flow, increased risk of thrombus formation, and embolism 25,26 . Due to the unique hemodynamic changes occurring in patients with PVCs, irregular ventricular rhythm as well as variable coupling intervals can also cause stasis of blood flow and promote thrombus formation in the left atrial appendage 27 . Moreover, the ventricular contraction from PVCs could not provide an effective cardiac output as a result of mechanical ventricular dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%